Applying FOSS Support Vector Machine and Rough Sets on COVID-19 Cases Triage - Hansen, Vinícius; Henings, Kalyl; Santos, Gilmário Barbosa dos (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware), 2023)
Free and Open Source Software (FOSS) is attractive for various reasons, calling the attention of developers of systems applied on the field of primary health systems, specially in third world countries. Considering the recent COVID-19 pandemic, FOSS approach has an important role to play on the development of systems on epidemiological surveillance and triage of cases according to the level of priority and taking in account the uncertainty in diagnosis. This paper formulated a model using Support Vector Machine and Rough Sets that demonstrates a proficiency in discerning between COVID, Uncertain, and Normal cases for the triage of cases based on chest X-rays. The results depicts an accuracy of 91.82%.